SYNTHESIS OF HIGH-CLASS MECHANISMS OF VARIABLE STRUCTURE BASED ON DYNAMIC ANALYSIS - Ualiyev З.Г.; Ualiyev Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This paper presents the model of a high class variable structure mechanism. These mechanisms have not gained widespread acceptance in practice, despite obvious improvements in the ability to transmit motion and power. The article presents a synthesized high class mechanism. The block diagram of the formation of the mechanism is shown, the results of synthesis are presented. It is shown that with a relatively compact kinematic scheme, it is possible, with one drive, to create a system with several working links providing various technological operations, that is, on the basis of one mechanism, it becomes possible to create automatic mechanisms. In these studies, the development of a methodology for the dynamic design of the variable structure mechanism based on the analysis of dynamics and Абай атындағы ҚазҰПУ-нің ХАБАРШЫСЫ, «Физика-математика ғылымдары» сериясы, №1(73), 2021 ж. 111 assessment of the influence of nonlinear factors on the quality of the machine as a whole was carried out. To study the motion of such variable structure mechanism, mathematical modeling of dynamics with discontinuous coefficients and nonlinear external forces is used.